(untitled) - Stallings, William (Upper Saddle River, NJ, 2007)
This book provides a practical, up-to-date, and comprehensive survey of network-based and Internet-based security applications and standards. Covers e-mail security, IP security, Web security, and network management security. Includes a concise section on the discipline of cryptography–covering algorithms and protocols underlying network security applications, encryption, hash functions, digital signatures, and key exchange.
An ninh mạng
Keywords: Computer networks,Mạng máy tính,Database management; Security measures,An toàn dữ liệu